ADVANCEMENTS IN SUSTAINABLE FABRIC PRODUCTION: A REVIEW OF TECHNOLOGIES AND FUTURE PROSPECTS - Azra Mushtaq (PT. Radja Intercontinental Publishing, 2025)
Sustainable fabric production has emerged as a critical area of focus in the textile and garment industry due to its potential to significantly reduce environmental impact. This review highlights recent advancements in sustainable fabric technologies, including the adoption of bio-based materials, innovative recycling techniques, and eco-friendly processing methods. It examines the transition from conventional to sustainable practices, providing a comparative analysis of their environmental footprints. Additionally, the paper explores the integration of biotechnology and chemical recycling in fabric production, showcasing their transformative potential. Case studies of industry leaders are presented to illustrate practical applications and benefits. The paper concludes with an exploration of challenges and future prospects, emphasizing the need for innovation and collaboration to drive sustainability in fabric production.